Survival Analysis in LGD Modeling - Jiří Witzany; Michal Rychnovský; Pavel Charamza (European Financial and Accounting Journal, 2012)
The paper proposes an application of the survival time analysis methodology to estimations of the Loss Given Default (LGD) parameter. The main advantage of the survival analysis approach compared to classical regression methods is that it allows exploiting partial recovery data. The model is also modified in order to improve performance of the appropriate goodness of fit measures. The empirical testing shows that the Cox proportional model applied to LGD modeling performs better than the linear and logistic regressions. In addition a significant improvement is achieved with the modified “pseudo” Cox LGD model
Keywords: C14; G21; G28; 650; Regulatory capital; Recovery rate; Loss given default; Credit risk; Correlation